Effect of pH and hydroxyapatite-like layer formation on the antibacterial properties of borophosphate bioactive glass incorporated poly(methyl methacrylate) bone cement - Hageman, Kara A.; Blatt, Rebekah L.; Kuenne, William A.; Brow, Richard K.; McIff, Terence E. (Frontiers in Bioengineering and Biotechnology, 2024)
Infection is a leading cause of total joint arthroplasty failure. Current preventative measures incorporate antibiotics into the poly(methyl methacrylate) (PMMA) bone cement that anchors the implant into the natural bone. With bacterial resistance to antibiotics on the rise, the development of alternative antibacterial materials is crucial to mitigate infection. Borate bioactive glass, 13-93-B3, has been studied previously for use in orthopedic applications due to its ability to be incorporated into bone cements and other scaffolds, convert into hydroxyapatite (HA)-like layer, and enhance the osseointegration and antibacterial properties of the material. The purpose of this study is to better understand how glass composition and change in surrounding pH effects the composite's antibacterial characteristics by comparing the incorporation of 30% wt/wt 13-93-B3 glass and pH neutral borophosphate bioactive glass into PMMA bone cement. We also aim to elucidate how HAlike layer formation on the cement's surface may affect bacterial adhesion. These studies showed that 13-93-B3 incorporated cements had significant reduction of bacterial growth surrounding the composite beyond 24 hours of exposure when compared to a neutral borate bioactive glass incorporated cement (p<0.01) and cement only (p<0.0001). Additionally, through soaking cement composites in simulated body fluid and then exposing them to a bioluminescent strand of staphylococcus aureus, we found that the presence of a HA-like layer on the 13-93-B3 or pH neutral glass incorporated cement disks resulted in an increase in bacterial attachment on the composite cement's surface, where p<0.001, and p<0.05 respectively. Overall, our studies demonstrated that borate bioactive glass incorporated PMMA bone cement has innate antimicrobial properties that make it a promising material to prevent infection in total joint arthroplasties.